Coefficient inequality for certain class of close-to-convex functions dependent on a real parameter / Nonis Airina Mohd Arshad, Nuraliah Yasmin Md Nasir and Nurzahidah Zamri - Mohd Arshad, Nonis Airina; Md Nasir, Nuraliah Yasmin; Zamri, Nurzahidah (2024)
The geometric functions theory of complex analysis is the basis of studying analytic univalent functions and investigating the geometric properties inherent in specific classes of analytic functions. However, this area of study faces significant challenges since only a small percentage of researchers are interested in discovering the properties. It might involve complex mathematical concepts, complex proofs, or abstract logic, which makes it difficult for many researchers to work on because of its level of difficulty. In addition, many researchers deal with difficulties in selecting suitable methods to manage mathematical analysis of their study.